Perubahan Sensitivitas Indera Perasa pada Anak dengan Obesitas - Angelique Agatha Suzanne; Gracia J M T Winaktu; Helena Fabiani; Luciana Budiati Sutanto (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2022)
Obesity is one of the most serious international health problems. According to WHO, obesity in Asia Pacific is defined by a body mass index of 23–24.9 kg m−2.1. Children are categorized as under 18 years of age. Obesity in children is a global health problem that has a negative impact on children's growth and development, and can even increase comorbidities in later life. In obesity, it is suspected that there is a change in the sensitivity of the sense of taste which can cause changes in diet and weight. This literature study aims to determine changes in the sensitivity of the sense of taste in obese children. The method used in this study is by searching journals that were conducted on 3 journal databases, namely PubMed, Google Scholar and Cochrane Library. Obtained 5 journals that meet the research criteria. Based on the study, obese subjects had more difficulty in correctly identifying different taste than normal weight kontrols resulting in a lower total score overall. Concluded that there is a change in the sensitivity of the sense of taste in children with obesity where the child has a lack of ability to taste sour, salty (umami) and sweet.